2022
DOI: 10.3390/mi13122049
|View full text |Cite
|
Sign up to set email alerts
|

Holographic Microwave Image Classification Using a Convolutional Neural Network

Abstract: Holographic microwave imaging (HMI) has been proposed for early breast cancer diagnosis. Automatically classifying benign and malignant tumors in microwave images is challenging. Convolutional neural networks (CNN) have demonstrated excellent image classification and tumor detection performance. This study investigates the feasibility of using the CNN architecture to identify and classify HMI images. A modified AlexNet with transfer learning was investigated to automatically identify, classify, and quantify fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Rana et al [ 93 ] applied ML in radar-based imaging for breast lesion detection. Wang [ 11 ] proposed a modified AlexNet with transfer learning to automatically detect, classify, and quantify different high-resolution microwave imaging breast images. The proposed transfer learning network achieved 100% accuracy in identifying and classifying HMI images, demonstrating promising applications in microwave breast imaging.…”
Section: Microwave Breast Imaging Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rana et al [ 93 ] applied ML in radar-based imaging for breast lesion detection. Wang [ 11 ] proposed a modified AlexNet with transfer learning to automatically detect, classify, and quantify different high-resolution microwave imaging breast images. The proposed transfer learning network achieved 100% accuracy in identifying and classifying HMI images, demonstrating promising applications in microwave breast imaging.…”
Section: Microwave Breast Imaging Techniquesmentioning
confidence: 99%
“…This enables the identification of malignant cells, which is crucial for an accurate diagnosis. Although holographic microwave imaging (HMI) algorithms have shown potential for breast cancer detection, further development, and validation are necessary before these techniques can be implemented in clinical trials [8][9][10][11][12][13]. Some MBI systems have already reached the clinical trials stage, as shown in Figure 2 [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Transfer learning addresses this challenge by allowing the transfer of knowledge from larger and more diverse datasets. Models pre-trained on millions of images can be adapted for breast cancer detection, even when the specific dataset is relatively small [54,55]. This increases the efficiency of model training and enables the development of robust classifiers, particularly in cases where collecting large-scale, specialized medical datasets is challenging.…”
Section: Transfer Learning For Breast Cancer Detectionmentioning
confidence: 99%
“…This kind of inverse problem is well-known in the scientific literature as the "inverse scattering problem" (ISP), and finding a stable solution is not trivial due to the issues of nonlinearity and ill-posedness [9]. Several inversion algorithms can be adopted to solve the ISP under consideration [10][11][12][13][14][15][16], and among them, neural networks seem to have better image reconstruction performance compared to traditional approaches [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Existing research in the field of microwave imaging has demonstrated the potential of artificial neural networks in reconstructing realistic breast images [20,21,23]. However, the reconstruction performance of these models in terms of both spatial resolution and retrieved complex permittivity values often remain insufficient to allow for accurate differentiation between breast tumors and the surrounding fibro-glandular tissue.…”
Section: Introductionmentioning
confidence: 99%